AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT BUAH KACANG KRATOK (PHASEOLUS LUNATUS) DAN KULIT BUAH KACANG GUDE (CAJANUS CAJAN) DENGAN METODE DPPH SERTA PENETAPAN KADAR TOTAL FLAVONOID DAN FENOL - Budiana, Wempi (Journal of Pharmacopolium, 2018)
Free radicals are molecules or atoms that have one or more unpaired electrons. Free radical compounds are very reactive and always try to find an electron pair so that the condition is stable. The presence of free radicals in the body is the cause of various chronic and degenerative diseases. This study aimed to determine the antioxidant activity and total flavonoid content and total phenolics from plant extracts of rind Phaseolus lunatus and Cajanus cajan. Extraction was carried out by using reflux method using solvents in stages, n-hexane, ethyl acetate, and ethanol. Evaluation of antioxidant activity was carried out by TLC and visible UV-Vis spectrophotometry with DPPH method. Determination of total flavonoid content, total phenolics using UV-Vis spectrophotometry. The results of antioxidant activity testing, the total content of flavonoids and phenols showed that ethanol extract of Cajanus cajan rind was the best with IC50 values of 22.07 µg / mL, 2.39 mg QE / 100 mg, 9.83mg GAE / 100 mg. The conclusion was that the ethanol extract of rind of Cajanus cajan had very strong antioxidant activity.